The Impact of Information Activity and Responsiveness on Export Investment Performance with the Mediating Role of International Channel Partner Selection through Word-of-Mouth Referral - Arefani, Marjan; Daghighi Masouleh, Gholamhossein; Samarbakhsh Tehrani, Ebn Sina; Samadi Largani, Mahmoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to investigate the impact of information activity and responsiveness on export investment performance with the mediating role of international channel partner selection through word-of-mouth referral. Methodology: This research is applied in terms of purpose and descriptive-survey in terms of data collection method. The statistical population of this study consists of managers of small and medium-sized export businesses in Tehran. A total of 380 valid questionnaires were obtained through simple random sampling based on Krejcie and Morgan’s table. Data collection methods in this study included both library research (reviewing articles, books, the internet, etc.) and field study. Field data were collected using the questionnaires developed by Ishii and Kikomori (2024). The validity of the questionnaire was confirmed through face and content validity, and its reliability was verified using Cronbach’s alpha and composite reliability. Data analysis was conducted using SPSS and Smart PLS software. Findings: The findings indicated that information activity, responsiveness, and international channel partner selection through word-of-mouth referral influence export investment performance. Moreover, information activity and responsiveness influence international channel partner selection through word-of-mouth referral. The mediating role of international channel partner selection through word-of-mouth referral in the relationship between information activity and responsiveness on export investment performance was confirmed. Conclusion: Therefore, information activity serves as a tool for reducing market entry costs and increasing the likelihood of export success.